An exploration of students' cyber threats perception in the digital age - Donald Mothisi; Mujinga, Mathias (Indonesian Journal of Information Systems, 2025)
This study aims to investigate cyber threat awareness among students from a rural-based university and propose a model to enhance their awareness. Students rely on information and communication technologies (ICTs) for educational and personal activities. Students in rural areas may have less cybersecurity education and awareness than their urban counterparts. This can affect their awareness of malware, social engineering, and other cyber threats. It also heightens the challenges students face in mitigating security breaches. Data was collected using a survey to assess students' awareness of cyber threats. This assisted in determining students' knowledge, attitude, and behaviour (KAB) when engaged in online activities. The results indicated that less than 20 per cent of the students are aware of threats like Trojan horses, phishing, and keyloggers. The limited awareness of these threats could negatively impact students' ability to protect their information resources. It is recommended that rural-based students are continuously made aware of cyber threats. This study proposes the student online threat awareness model (SOTAM) to enhance cyber threat awareness among students.